A study on consumer banking: |recent developments in marketing of bank services in Turkey - Güleşçi Pekuysal, Petek. (Thesis (M.A.) - Bogazici University. Institute of Social Sciences, 1997., 1997)
The purpose of this study is to identify the consumer banking products in Turkey, to find out about the awareness of consumers to these products, to discover their utilization frequencies and the attitudes of consumers towards these services. Consumer banking will also be investigated from the viewpoint of bank managers during the course of this study. After a review of literature on the subjects of marketing of services in general and marketing of bank services, the consumer banking products around the world will be presented. Consumer banking products in Turkey ~111 also be presented which summarizes the results of the interviews made with bank managers. For the purpose of the study, a descriptive research focusing on bank customers was conducted in Istanbul. Analyses were performed on data collected from 210 questionnaires by using SPSSIPC version 5.0. program. The first group of findings of this study are the results of the interviews made with bank managers. These findings shed some light on the status of consumer banking in Turkey today, including the types of services offered, the criteria for giving these services, the reasons for choosing to offer these services as well as the marketing policies and procedures of banks in Turkey. The second group of findings of the study are associated with the field research conducted. One of the important findings is that consumer banking products are well known, among which ATM services are the most widely known and accepted one. Checks and credit cards are also well known and frequently utilized. The usage frequencies of home banking services and consumer ~ credits are moderate, while portfolio services are the ieast utilized consumer banking service offered. The findings of this study are expected to contribute to the Turkish literatUre on marketing of consumer banking products, by offering information about consumer banking products, about bank customers and their preferences, as well as serve bank managers by providing some important implications, and academicians by presenting the need for further research.
Keywords: Bank marketing -- Turkey.